Minimizing Oxygen Permeation in Metal-Chelate Flow Batteries. (25th June 2020) - Robb, Brian H.; Waters, Scott E.; Marshak, Michael P.
Abstract : Coulombic efficiency (CE) losses within redox flow batteries (RFBs) decrease system performance and can indicate possible long-term capacity fade. Here, we discuss improvements made to lab-scale redox flow battery construction and operating conditions. The augmented RFB set-up limits the oxidation of highly reducing species by minimizing atmospheric oxygen permeation and subsequently demonstrates improved performance. The addition of sealed compression fittings, peristaltic pumps, and the operation of the battery in an N2 glovebox leads to near quantitative CE for a chelated Cr electrolyte, improving from previously utilized systems which operated as low as 93.2% CE at low current densities. The importance of preventing O2 permeation is exemplified and the battery efficiencies in an ambient atmospheric and nitrogen environment with different electrolyte reservoir apparatuses are contrasted. Possible sources of the remaining CE losses are also discussed.